Analyzing the effects of digital marketing on brand awareness among internet users - Karen Karen; Immanuel Zai (Fakultas Ekonomika dan Bisnis, Universitas Kanjuruhan Malang, Indonesia, 2022)
Information technology advancements have influenced how marketing is carried out in the sector with that, a variety of platforms and methods for raising consumer brand awareness. Digital marketing strategies such as advertising, social media marketing, content marketing, email marketing, and website marketing are well-known and used across a variety of industries in our fast-evolving technology. This article provides a thorough analysis of how various digital marketing strategies related to brand recognition. In light of this, the study design for this work is comparative causal, and the primary data used were those that were gathered from 273 consumers of digital media in the province of Riau Island and evaluated using the SmartPLS program. The theory was put to the test, and the results revealed a significant positive association between internet advertising and brand recognition. The study can be further expanded using data from various age groups, geographic locations, and other digital marketing strategies which wasn’t further studied in this study.